Risk factors for loneliness in family caregivers of people with dementia and enduring mental health conditions during the COVID‐19 pandemic in Latin America. (20th December 2022) - Leon, Tomas; Miranda‐Castillo, Claudia; Slachevsky, Andrea; Tapia‐Muñoz, Thamara; Olavarria, Loreto; Castro, Loreto; Pinto, Alejandra; Chen, Yaohua Sophie; Leroi, Iracema; Lawlor, Brian; Duran‐Aniotz, Claudia; Grycuk, Emilia; et al.
Abstract: Background: During the COVID‐19 pandemic, loneliness has increased in the general population due to government measures to contain the spread of the disease. In Latin America (LA), caregiving is most often delivered informally by family members Family caregivers often face mental health challenges linked to their caregiving role and their social context. Pandemic‐related social restrictions have been especially detrimental for older people with dementia or other brain health challenges, as well as their family caregivers. We aimed to investigate the associations of loneliness, social isolation and care burden in these family caregivers. Method: We undertook a cross‐sectional survey of over 300 informal caregivers of people with dementia or enduring mental health problems living in 4 Latin American countries, Mexico, Brazil, Chile, and Peru. We categorized loneliness into 3 groups 'low', 'moderate' and 'severe loneliness'. Here, we analyzed factors related to changes in the prevalence of moderate and severe loneliness before and during the pandemic using a longitudinal multinomial logistic regression model. Result: During the pandemic, there was a significant increase in loneliness prevalence (p<.001) among caregivers in Latin America, with more people having moderate (6.25% pre‐pandemic; 17.67% mid‐pandemic) and severe loneliness (2.78% pre‐pandemic; 15.19% mid‐pandemic). Gender differences in the prevalence of loneliness or higher levels of loneliness among dementia caregivers compared to caregivers of other conditions were not seen. The regression model revealed that the increment in risk for moderate loneliness during the pandemic was related to caregivers' age, level of education, and social contact/isolation. Increased risk for severe loneliness was related to caregivers' social contact during the pandemic and perceived mental health. Conclusion: Public health interventions regarding COVID‐19 pandemic should consider increased loneliness in Latin‐American caregivers. This population will need both, short and long‐term mental health and practical support. Next steps include gathering more evidence on specific risk factors for loneliness and its impact on caregivers' physical and mental health.